Elite support for peace agreements: evidence from Colombia. (2nd January 2022) - Bohigues, Asbel; Rivas, José Manuel; García, Sergio
ABSTRACT: In 2016, Colombians in a plebiscite rejected the Peace Agreement between the government and FARC, although a new version was approved by Congress later that year. Attention has been paid to this plebiscite and public opinion, but little empirical evidence has been offered on the attitudes of the Colombian political elites who ultimately approved the Agreement. Drawing on elite surveys made before (2014) and after (2018) the Agreement, this is the first article to address legislators' support for political participation of former guerrilla, and reductions of their sentences and penalties. Results show that pro-military and right-leaning legislators were less supportive of political participation, while female and lower-income legislators were less supportive of reductions in sentences. However, between 2014 and 2018 the effect of political attitudes loses strength, as opposed to sociodemographics. We argue that this was due to mixed signals sent by the new government regarding implementation of the Agreement.